L’Observatoire photographique national du paysage : transformations d’un modèle et hypothèses renouvelées de paysage - Frédérique Mocquet (Projets de Paysage)
In the context of the landscape’s extreme prominence as a discourse, composition, and image, initiatives for the photographic observation of the landscape are developing in France. These approaches inherited from the Observatoire photographique national du paysage (OPNP), take inspiration from a “method” which has been put forward as a “model”. The creation of so many Photographic Observatories of the Landscape presents a paradox. Why is this initiative such a success, given the difficulties encountered and the recurring criticism expressed by leading organisations concerning the implementation of this “tool”? This article seeks to shed light on the reasons behind this paradox by looking back at the context that gave rise to the OPNP experiment. The article also takes a critical look at the founding theoretical and conceptual principles (even those not formulated) which inspired a programme with such a strong rhetorical dimension and compares these principles with the systems implemented. A question arises concerning the possible reassessment of this approach after 25 years: Might not the “the OPNP heritage” be the continuation of an experimental programme the contributions, ambivalences, shortcomings and contradictions of which need to be re-examined today? Lastly, a specific initiative offers an interesting case study on the potential and perspectives for a re-contextualisation of the heritage and the potential for applying photographic observation to landscapes. “Paysages usagés, Observatoire photographique du paysage depuis le GR2013” (“Used Landscapes, A Photographic Observatory of the Landscape from the GR2013 Trail”), which was born of the initiative of a critical reinterpretation of the method by photographers Bertrand Stofleth and Geoffroy Mathieu, proposes a re-evaluation of the perspectives of photographic observation focusing on the aesthetic experience of the landscape as a plural mediation placing an artistic project at the heart of territorial planning.